Answer:
[tex]f(x)=\sqrt{37x^{2}-2x+26}[/tex]
Step-by-step explanation:
we know that
To compute the required distance, using properties of triangles
Applying the Pythagoras Theorem
see the attached figure to better understand the problem
[tex]PT^{2}=(6x-1)^{2}+(x+5)^{2}[/tex]
convert to expanded form
[tex]PT^{2}=36x^{2}-12x+1+x^{2}+10x+25[/tex]
[tex]PT^{2}=37x^{2}-2x+26[/tex]
square root both sides
[tex]PT=\sqrt{37x^{2}-2x+26}[/tex]
Convert to function notation
[tex]f(x)=\sqrt{37x^{2}-2x+26}[/tex]